Les politiques du tracteur chez les Wichís du Chaco argentin - Alberto Preci; Marco Flamini (EchoGéo)
Machines and their uses are rarely the focus of research on indigenous worlds. Against this background, this article describes the life-patterns of tractors among the Wichis of the Argentine Chaco. Our hypothesis is that these machines, caught in a web of clientship relations, play a central role in contemporary political reordering. They not only engage in the evolution of interethnic relations, but they also catalyze tensions amongst the communities. By following two tractors on the ground and looking at their daily lives, we show how they have become a political tool that can also be used incidentally for farming.